Management of Chronic Gingivitis with localized periodontitis by Nonsurgical (Phase I) Periodontal Therapy- A Case Report (Update Dental College Journal, 2018)
Periodontitis is a chronic inflammatory disease of the periodontal tissues (periodontium) which surround and support the teeth, that results in attachment loss and alveolar bone destruction leads to ultimate tooth loss. It is caused by the bacteria present in dental plaque, which is a tenacious substance that forms on teeth and gingiva just after teeth are brushed. Periodontal treatment is aimed at controlling the infection in order to stop the progression of the disease and to be able to maintain a healthy periodontium. Mechanical debridement of supragingival and subgingival biofilms, together with adequate oral hygiene measures is the standard periodontal therapy. This mechanical subgingi- val biofilm debridement consists of an initial (nonsurgical /phase I) phase involving scaling and root planing (SRP) and the elimination of plaque retentive factors, followed by a surgical phase (if needed) including the elevation of a tissue flap and bone remodeling in further stages. The adjunct use of antibiotics has proven to additionally improve the outcome of periodontal treatment. A clinical case of a 40-years-old male patient with generalized severe chronic periodontitis with localized gingival swell- ing was treated with nonsurgical (phase I) periodontal therapy that was confined to oral hygiene instruction (OHI), SRP with an adjunct antimicrobial regimen.Update Dent. Coll. j: 2017; 7 (2): 33-37